Beyond survival to domination: Brucella’s multilayered strategies for evading host immune responses - Wei, Zhimeng; Zhang, Shuai; Wang, Xingya; Bai, Jie; Wang, Hui; Yang, Yuanchao; Zhai, Jingbo (Frontiers in Microbiology, 2025)
Brucella is an intracellular parasitic bacterium with a wide host range. It can infect terrestrial mammals, including domestic animals such as cattle and sheep, as well as wild animals like elk and bison. It also infects marine mammals, and amphibians. These diverse hosts form the basis for the classification of Brucella into different species. It can invade multiple cell types, including human cells such as monocytes/macrophages, dendritic cells (DCs), and trophoblasts; primary animal cells such as murine and bovine macrophages, and canine trophoblasts; and established cell lines such as HeLa and Vero cells. Among these, macrophages, DCs, and trophoblasts are the main target cells. Brucella employs a variety of strategies to evade host defenses: (1) obstruction of pattern recognition receptors; (2) formation of replicative Brucella-containing vacuoles following entry into host cells; (3) suppression of innate immunity through manipulation of autophagy, endoplasmic reticulum stress, inflammasomes, pyroptosis, apoptosis, ferroptosis, and pathways including cGAS-STING; and (4) inhibition of adaptive immunity through reduced antigen presentation. Compromised innate and adaptive immunity allows Brucella to replicate and survive within host cells, leading to chronic infections that are difficult to eradicate. Notably, Brucella suppresses host immunity by producing virulence factors that inhibit cytokine release and antigen presentation, and that interfere with critical signaling pathways such as programed cell death, ultimately downregulating both innate and adaptive immune responses. Collectively, these features have made the development of treatments and vaccines for brucellosis particularly challenging. While a better understanding of virulence factors is key to the effective prevention and control of brucellosis, many pathogenic mechanisms remain unclear. In this systematic review, we focus on the interactions between Brucella and the host immune system. Specifically, we examine the roles of the following factors in Brucella infection: lipopolysaccharides, flagella, the type IV secretion system (T4SS), effector proteins secreted by the T4SSs and non-T4SS, outer membrane proteins, phosphatidylcholine, mechanisms of intracellular survival, pathogen-associated molecular patterns, pattern recognition receptors, subversion of selective autophagy, endoplasmic reticulum stress pathways, inflammasomes, pyroptosis, apoptosis, ferroptosis, and the cGAS-STING pathway. We anticipate that this overview will offer new insights for research and development into drugs and vaccines for brucellosis.